The impacts of China's fund policy on waste electrical and electronic equipment utilization. (1st April 2020) - Liu, Guangfu; Xu, Yi; Tian, Tingting; Wang, Tao; Liu, Yang
Abstract: Waste electrical and electronic equipment utilization is increasingly regulated in China, through the implementation of fund policy, to promote sustainable development. This research discusses the economic and social impacts of the fund policy by employing a game-theory-based model and simulating a new fund reduction policy to achieve multi-objective optimization. The results suggest that (i) the fund policy may create trade-off problems between remanufacturing profits and economic burdens onto primary manufacturers; (ii) The manufacturers are not as favorable to eco-design as expected, resulting in remanufacturers' overdependence on government subsidies. Strategically, a fund reduction policy is devised for addressing the negative effects of the fund policy. This reduction policy can provide better incentives for manufacturers to carry out eco-design. It may also improve the profits of both manufacturers and remanufacturers, social welfare and greatly reduce the environmental costs. The findings would provide insights into e-waste management and recycling policies in China and the developing world as in general. Graphical abstract: Image 1 Highlights: China's Fund policy was investigated and optimized based on game theory. Fund policy causes conflicting interests between manufacturers and remanufacturers. Government's incentives to manufacturers can improve eco-design level. Fund reduction policy improves enterprises' profits and reduces environmental costs. Fund reduction policy significantly enhances social welfare.